The geopolitics of Gazprom’s pipelines - Kosowska, Katarzyna; Kosowski, Piotr (My University, 2016)
The natural gas market over the years has been strongly dependent on pipeline transport and based on it a gas market was created and functioned. For this reason, unlikely to the oil market, the global gas market was not created and did not function, but only national, regional and continental markets separated from the others functioned. The consequence of this situation is the fact that the key importers of Russian gas abroad are the CIS and European countries. The Kremlin hiding behind Gazprom has consistently pursued a policy of diversification of export transmission system, designed to eliminate “problematic” transit countries such as Ukraine. That aim can be accomplished by completed and planned pipelines’ diversification projects.
AGH Drilling, Oil, Gas
Keywords: Gazprom; pipelines; geopolitics; gas market; Russia